BUSINESS DEVELOPMENT STRATEGY USING THE BUSINESS MODEL CANVAS APPROACH AT NH STUDIO IN SINJAI DISTRICT - Nanda Pratiwi; Agus Syam, Asmayanti (Adisam Publisher, 2024)
This research aims to create a business development strategy by transforming the NH Studio business model in Sinjai Regency using the Business Model Canvas approach. The research method used is descriptive qualitative research using data collection methods through observation, in-depth interviews and documentation of a research object. Through interviews with stakeholders at NH Studio, conclusions were drawn based on several key aspects. The result of NH Studio's business development strategy is an increase in value in the nine elements of the Business Model Canvas resulting in new strategies ranging from Customer Segment to Cost Structure. Diversification of services is also recommended so that NH Studio is able to compete and overcome existing problems